Increased brightness assimilation in rod vision - Pablo A. Barrionuevo; Alexander C. Schütz; Karl R. Gegenfurtner (iScience)
Summary: Our visual system uses contextual cues to estimate the brightness of surfaces: brightness can shift toward (assimilation) or away from (contrast) the brightness of the surroundings. We investigated brightness induction at different light levels and found a potential influence of rod photoreceptors on brightness induction. We then used a novel tetrachromatic display to generate stimuli differentially exciting rods or cones at a fixed light adaptation level. Under rod vision, brightness assimilation was enhanced while brightness contrast was not altered in comparison to cone vision. We ruled out that this effect was mediated by the low resolution of night vision. Our findings suggest that rod vision affects the high-level interpretation of visual scenes that results in differences in brightness assimilation but not contrast. Our results imply that the visual system employs more perceptual inferences under rod vision than under cone vision to solve visual ambiguities in complex spatial displays.